Estudio de la calidad de sitio para Pinus radiata D. Don. En las plantaciones de Granja Porcón, Cajamarca. - Huaripata Chilón, Davidad (2013)
The principal a1m of this investigation was to determine the quality of site of the plantations of Pinusradiata D. Don, and the influence of the ecological factors in the modelamiento of his growth of the height; the above mentioned plantations are located in the CAT Atahualpa Jerusalem to 3,350 msnm in the province and Cajamarca's department. The methodological applied process was the estimation of the "Index of site ". For this the behavior ofthe variables was analyzed dendrológicas and ecological (such as the slope, the exhibition and the characteristics edáficas) of each of 14 plots established in the area of study. F or the estimation of the Quality of Site and of the Model of Growth of the Pinusradiata there were applied the technologies of regression and correlation between the dependent variable (height) and the independent variables (ecological variables). All these mentioned analyses and others more allowed us to determine three Qualities of Site (CS-I, CS-II and CS-III) and the Model ofGrowth (formula) ofthe Pinusradiata. The latter will allow us to detennine qualities of site and to estímate the growth in height that the Pinusradiata might have to the age of 20 years in other zones across the technologies of extrapolation. The certain model expresses of the following way: Y= 27,162- 5,01(pH) + 0,31(MO) -1,572(N) +O, 059(PE) + 0,255(CC) Dónde: pH =Potencial de hidrogeno; MO =Materia Orgánica; N = Nitrógeno; PT Profundidad Total; CC =Capacidad de Campo y 27,169 =Constante.